Analisis Penerapan E-Government dan Perubahan Interaksi Sosial setelah Mediatisasi di Desa Karang Bajo, Lombok - Sari, Wulan Purnama (Universitas Semarang, 2017)
In Indonesia, the digital era is not only brings difference for people residing in urban areas, but also in rural areas that do not have adequate access in terms of resources. As one example is a village in the province of Lombok named Karang Bajo. Karang Bajo village apply it s government with the use of technology and new media, in other words Karang Bajo Village has introduced a system of E-Government. This is in line with the concept mediatization which can be interpreted as the most important concepts to understand the importance of the media on culture and society. The study was conducted using a qualitative approach and case study method. The results from this research is E-Government applied in Karang Bajo village is still in the billboards stage with primaly puspose because constitution UU No. 6 (2014). The presence of E-Government didn t bring any changes in society s social interaction.